The Antidepressant-Like and Analgesic Effects of Kratom Alkaloids are accompanied by Changes in Low Frequency Oscillations but not ΔFosB Accumulation - Buckhalter, Shoshana; Soubeyrand, Eric; Ferrone, Sarah A.E.; Rasmussen, Duncan J.; Manduca, Joshua D.; Al-Abdul-Wahid, M. Sameer; Frie, Jude A.; Khokhar, Jibran Y.; Akhtar, Tariq A.; Perreault, Melissa L. (Frontiers in Pharmacology, 2021)
Mitragyna speciosa (‘kratom’), employed as a traditional medicine to improve mood and relieve pain, has shown increased use in Europe and North America. Here, the dose-dependent effects of a purified alkaloid kratom extract on neuronal oscillatory systems function, analgesia, and antidepressant-like behaviour were evaluated and kratom-induced changes in ΔFosB expression determined. Male rats were administered a low or high dose of kratom (containing 0.5 and 1 mg/kg of mitragynine, respectively) for seven days. Acute or repeated low dose kratom suppressed ventral tegmental area (VTA) theta oscillatory power whereas acute or repeated high dose kratom increased delta, and reduced theta, power in the nucleus accumbens (NAc), prefrontal cortex (PFC), cingulate cortex (Cg) and VTA. The repeated administration of low dose kratom additionally elevated delta power in PFC, decreased theta power in NAc and PFC, and suppressed beta and low gamma power in Cg. Suppressed high gamma power in NAc and PFC was seen selectively following repeated high dose kratom. Both doses of kratom elevated NAc-PFC, VTA-NAc, and VTA-Cg coherence. Low dose kratom had antidepressant-like properties whereas both doses produced analgesia. No kratom-induced changes in ΔFosB expression were evident. These results support a role for kratom as having both antidepressant and analgesic properties that are accompanied by specific changes in neuronal circuit function. However, the absence of drug-induced changes in ΔFosB expression suggest that the drug may circumvent this cellular signaling pathway, a pathway known for its significant role in addiction.